A study of polysemy on Chinese body-part terms tou ‘head’ and yan ‘eye’ : a cognitive approach / Lv Yetong - Lv, Yetong (2014)
Polysemy, or the association of two or more related meanings with a single linguistic form (Taylor, 1995, p.99), is ubiquitous in language and receives attention from many linguistic disciplines. Cognitive linguists interpret the meanings of polysemous words based on conventional conceptual structures, as the identification of polysemy involves the conceptualization of everyday life. Based on the principles of cognitive linguistics, this study analyzes polysemy through an in-depth examination of Chinese body-part terms, namely tou „head‟ and yan „eye‟, in order to unfold the internal relationships among the meanings of polysemous words. According to the findings, first, the original or literal meanings of body-part terms tou „head‟ and yan „eye‟ refer to the body parts „head‟ and „eye‟. Each body-part term is composed of various related meanings; among these are a prototypical or literal meaning and peripheral or extended meanings. Second, the formation of meanings of each body-part term is a process of category extension, and metaphor and metonymy are two important cognitive mechanisms for category extension. Third, this study analyzes the structural patterns of literal and extended meanings of tou „head‟ and yan „eye‟. The meanings of each body-part term are associated with different parts of speech, establishing highly entrenched structural patterns to directly differentiate literal and extended meanings of each body-part term. Based on the cognitive-linguistic analysis of Chinese body-part terms, the meanings of a polysemous word are closely related and form a prototype-based semantic network. However, the polysemous meanings have few attributes in common and have their own representations respectively. Also, they are not interpreted independently but are contextually modulated. A cognitive-linguistic study of Chinese body-part terms will offer insight into the internal construction of polysemy, foster better understanding of various meanings of Chinese body-part terms, and benefit communication among speakers who take Chinese as a native or foreign language. Keywords: polysemy, cognitive linguistics, body-part terms, prototype, metaphor, metonymy, structural pattern